Political Economy Analysis of 10 KPSPAMS Associations (Association of Drinking Water and Sanitation System Management Groups) in Indonesia - Avessina, Mohammad Jibriel; Wibowo, Agung; Bimo, Widhi Ariyo; Syafiq, Muhammad Daris (prodima@fe.uika-bogor.ac.id, 2025)
The implementation of Sustainable Development Goal (SDG) 6 entails the provision of safe, affordable, and high-quality clean water access. The primary objective of this goal is to ensure universal access to clean water and adequate sanitation for all individuals by 2030. This research conducted a qualitative methodology using triangulation data collection techniques, which covered interviews, Focus Group Discussions, and Desk Reviews of documentation from 10 KPSPAMS Associations throughout Indonesia regarding their implementation of effective organizational culture practices on Rural Water Services in Indonesia. The findings of this research indicate that organizational culture practices are generally functioning effectively. However, regarding management principles, several aspects need to be enhanced to facilitate local government involvement in establishing optimal support for community access to clean water.